Frontiers in Earth Science - Editor's Choice 2017 - Valerio Acocella (Frontiers Media SA, 2018)
2017 has been an exciting year for our innovative open access journal Frontiers in Earth Science: many new articles have been published and are now indexed in Web of Science (ESCI), new sections have opened for submissions (including Solid Earth Geophysics), and our Editorial Board has been successfully leading the peer review process and providing comprehensive reviews to our authors. Have a look at our archive to read about the feeding habits of dinosaurs, human influence on in the African humid period, volcanic hazard models, or how glaciers flowing into the ocean surrounding Greenland have changed over time! Launched at the end of 2013, our Journal consists of several specialties whose number has increased with time and currently stands at 19, also including a few specialties co-listed in other fields (https://www.frontiersin.org/journals/earth-science#). The present selection is not exhaustive as new ones are being launched and/or are under consideration for development. This growth has been paralleled by a yearly increase in the number of contributions and the Editorial Board members, reflecting the health of the Journal. Now also indexed in Web of Science - Emerging Sources Citation Index (ESCI), Frontiers in Earth Science is ambitious to become the leading open access journal in its field. The idea of creating an Editor's Choice eBook has been in our minds for a while as we wanted to create an environment for the Chief Editors to highlight their choice of representative papers in the Journal - we are happy to present now our first edition. The eBook offers a quick, though representative, window into the different specialties, giving additional visibility to some of the most interesting studies published in 2016 and 2017. It provides a glimpse into the state of the art of Earth Science on the cusp of 2020. Earth Science studies the different spheres of the Earth (geosphere, atmosphere, hydrosphere and, partly, biosphere) and, as such, it provides a holistic perspective of our planet. This discipline, in addition to understanding our environment, enables us to face major natural challenges, such as improving the management of natural resources, promoting environmental sustainability and forecasting and managing natural hazards (Acocella, 2015, and references therein). On this basis, the contributions grouped in this eBook, even though appearing distinct in subject, methods, goal and impact, should be considered as different aspects of the same system. Indeed, the selection of these contributions aims to capture a multidisciplinary and common understanding of our planet, with its interconnected processes and challenges. It is important to note that, in many cases, it has not been easy to select a representative study per specialty, and thus the papers included in this eBook should therefore not be considered as the representative ones, but rather as a concise selection of key papers. We hope you enjoy reading our first edition of the Editor's Choice eBook! Jessica (Journal Manager), and Valerio (Field Chief Editor)